Anticiparse al error. Dudas y recursos sobre fármacos en Castilla y León. - Xosé Manuel Meijome Sánchez (Ene, 2015)
We wanted to know the doubts about the handling of drugs that appear to nurses of Castilla y León and discover the available resources for resolution. Using an "ad hoc" survey distributed by email, social networks and in two hospitals and a residence of the public system of Castilla y León. Most questions about drugs only occasionally occur. The decrease of the doubts with age and professional experience points to deficits in undergraduate training or changing work environment. Highlights the unequal distribution of resources support on drugs.